DESIGN & SIMULATION OF MEMS VARIABLE CAPACITOR FOR OPTIMUM ANTENNA TRANSMISSION - Mohd Faizol, Noor Azreen (Universiti Teknologi PETRONAS, 2011)
The purpose of this project is to design and simulate the impedance matching network or known as tuner which include MEMS variable capacitor that results in wider range of frequency. The wireless communications and MEMS are widely used in many applications such as Bluetooth, Global Positioning System (GPS) and internet modem for its benefits. Nowadays, wireless communication system and MEMS are developed every day. As the development of both industries grows, some integrity signal issues such as reflection and impedance mismatch which caused important signal loss become crucial. Signal loss is the phenomenon happen when the transmitted signal is not fully received by the receiver during the transmission session due to impedance mismatched. Therefore, to reduce any signal loss due to impedance mismatch between transmitting and receiving antenna and with the connected systems, an impedance matching network or known as tuner is required. Since the demand for faster and smaller communication systems are increasing, MEMS technology is the best choice in designing this tuner since MEMS is small in size, light weight and enhanced performance and reliability. So, the MEMS tuner is designed in this project where the device has capability to tune and match the input impedance of the source with the load impedance of the antenna. Basically this project is divided into two parts which is communication systems and MEMS. For communication part, the impedance matching analysis and parameter determination is done using MATLAB and ADS. The analysis shows the range of capacitance value to reduce the signal loss by almost 50% is 5 pF to 10 pF. For MEMS part, the MEMS structure design and simulation is done in the MATLAB with reference capacitance value from the communication part which is 5 pF to 10 pF. From the MA TLAB simulation result, the device is shown to be driven by 110 V and 71.4 pN of electrostatic force to move the parallel plate to achieve 3 pF to 8 pF of capacitance value. This range of capacitance lies within the expected range of capacitance. So, the MEMS variable capacitor can be tuner that reduces the signal loss by 50% with the 3 pF to 8 pF range of capacitance.